A study on the stress concentration factor induced in double countersunk holes due to uniaxial tension - Gharaibeh, Mohammad A. (Zielona Góra: Uniwersytet Zielonogórski)
Finite element and response surface methods were utilized to investigate the stress concentration factor induced in isotropic rectangular plates with two identical countersunk rivet holes due to uniaxial tension. In this investigation, the finite element model was constructed using ANSYS software and used to produce stress concentration factor (SCF) data.
Keywords: double countersunk holes; stress concentration factor; Finite Element Method (FEM); response surface methodology; uniaxial tension